Effects of different tillage systems and mowing time on nutrient accumulation and forage nutritive value of Cyperus esculentus - Du, Yi; Zhang, Yulin; Chai, Xutian; Li, Xiangyi; Ullah, Abd; Islam, Waqar; Zhang, Zhihao; Zeng, Fanjiang (Frontiers in Plant Science, 2023)
Revealing the complex relationships between management practices, crop growth, forage nutritive value and soil quality will facilitate the development of more sustainable agricultural and livestock production systems. Cyperus esculentus is known as the king of oil crops and high-quality forage. However, there is little information about the effects of different planting modes {continuous cropping (CC)/rotation cropping (RC)} and initial mowing time on the plant nutrient accumulation and forage nutritive value. Here, in a field experiment, we designed two planting patterns, C. esculentus CC and C. esculentus - wheat RC. The leaves, tubers, roots, and soil samples were collected at three mowing times (on the 78th, 101th, and 124th days after seed sowing). Results revealed that RC significantly increased the total nitrogen (TN) and potassium (TK) content of the tuber (p<0.05), while significantly decreased the TN, total phosphorus (TP), crude protein (CP), and acid detergent fiber (ADF) contents of the leaves. Correlation analysis showed that soil pH was negatively correlated with TN content in leaves, tubers, and roots. The structural equation model showed that the soil pH directly affected the plant nutrient accumulation and forage nutritive value (=0.68) via regulating these properties by changing soil available nutrients, anions, cations, and total nutrients. Overall, we propose that RC for C. esculentus-wheat is should not be recommended to maximize tubers and forage yield.